Effects of Heavy Metal Contamination on Fungal Diversity in Pinus brutia Shoots - Melike Cebi Kilicoglu (BioResources, 2024)
The effects of heavy metal pollution have become a significant global issue in recent years. The primary objective of the present study was to compare the heavy metal concentrations in Pinus brutia shoots grown in an organized industrial zone (OIZ) and a forested area (Adalar) and to examine how these heavy metals affect fungal microbiota. The results achieved here showed that Ni and V concentrations were lower than the detectable limits in both the Adalar and the OIZ region, whereas Se and Cu concentrations were lower than the detectable limits in the shoots collected from the Adalar. Concentrations determined in samples collected from the OIZ were approximately 6 times higher for Cr and 16 times higher for Zn in comparison to the samples collected from the Adalar. Metagenomic analysis revealed that the most common fungal genera were Aureobasidium, Gibberella, Hazslinszkyomyces, Alternaria, Cladosporium, Buckleyzyma, Lasiodiplodia, and Hormonema for the OIZ area and Hormonema, Aureobasidium, Alternaria, Cladosporium, Arthrinium, Fonsecazyma, and Truncatella for the Adalar region. In the future, this study may serve as a reference for the development of innovative strategies for the remediation of heavy metal pollution for a sustainable and clean environment using biological sources.